Assessment of atrial electromechanical interval using echocardiography after catheter ablation in patients with persistent atrial fibrillation - Chen, Xiaodong (J Biomed Res, 2016)
We sought to investigate variation of atrial electromechanical interval after catheter ablation procedure in patients with persistent atrial fibrillation using pulse Doppler (PW) and pulse tissue Doppler imaging (PW-TDI). A total of 25 consecutive in-patients with persistent atrial fibrillation, who restored sinus rhythm after ablation procedure, were recruited in our cardiac center. Echocardiography was performed on each patient at 2 hours, 1 day, 5 days, 1 month and 3 months after the ablation therapy, and atrial electromechanical delay was measured simultaneously by PW and PW-TDI. There was no significant difference between PW and TDI in measuring atrial electromechanical delay. However, at postoperative 2 hours, peak A detection rates were mathematically but nonsignificantly greater by PW-TDI than by PW. Second, there was a significant decreasing trend in atrial electromechanical interval from postoperative 2 hours to 3 months, but only postoperative 2-hour atrial electromechanical interval was significantly greater than atrial electromechanical interval at other time. Lastly, patients without postoperative 2-hour atrial electromechanical interval had a significantly longer duration of atrial fibrillation as compared to those with postoperative 2-hour atrial electromechanical interval, by the PW or by PW-TDI, respectively. In patients with persistent atrial fibrillation, atrial electromechanical interval may decrease significantly within the first 24 hours after ablation but remain consistent later, and was significantly related to patients’ duration of atrial fibrillation. Atrial electromechanical interval, as a potential predicted factor, is recommended to be measured by either PW or TDI after 24 hours, when patients had recovered sinus rhythm by radiofrequency ablation.